Analisis Metode Role Playing Dalam Pembelajaran Keterampilan Berbicara Bahasa Jawa Kelas III SD Negeri Keditan Magelang - Rizki Fatimah, Ana; Rinawati, Atim; Maryanto, Maryanto (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2022)
This study aims to determine how the use of the role playing method in learning Javanese language skills in class III SD Negeri Keditan. This study uses a qualitative approach by processing the data obtained in the field. The subjects of this study were the Principal, Class III Teachers and Class III Students. The research instrument used is to use data collection techniques through observation, interviews, documentation, and perform data analysis with data reduction, data presentation and then draw conclusions. The results of this study indicate (1) the use of the role playing method in learning skills includes determining material, determining roles, observers, then planning followed by practice and evaluation (2) the role playing method in learning Javanese speaking skills is said to be effective, namely the completion of student learning outcomes. , students are active in learning, the response is good and positive, and the teacher's ability to manage the class is categorized as good.